Spermatozoa Obtained From Alpaca vas deferens. Effects of Seminal Plasma Added at Post-thawing - Aisen, Eduardo G.; Huanca López, Wilfredo; Pérez Durand, Manuel G.; Torres Mamani, Edita; Villanueva Mori, Juan C.; Ousset, María J.; Medina, Víctor H.; Pérez Guerra, Uri H.; Huanca Mamani, Teodosio (Frontiers in Veterinary Science, 2021)
The viscous seminal plasma (SP) is currently the major impediment to handling ejaculates and then, the development of some biotechnologies in South American camelids. The vas deferens-collected spermatozoa from alpacas seems to be a useful technique to avoid this problem. On the other hand, SP contains a large protein component which has been implicated in the function of spermatozoa within the female reproductive tract. In this sense, the low fertility achieved using transcervical insemination with frozen-thawed spermatozoa in alpacas could be improved by adding SP. The aim of this study was to evaluate the effect of whole SP on some in vitro parameters of alpaca spermatozoa after freezing-thawing-process, and the fertility after artificial insemination. It would contribute to better understanding of the interaction of thawed sperm cells with SP. Spermatozoa were obtained by surgically diverted vas deferens. The samples were diluted with Tris-based extender, packaged in straws and frozen. At thawing, each straw was divided into two post-thawing conditions: with addition of 10% of PBS (control) or with 10% SP (treatment). The sperm cells were evaluated by means of dynamic parameters, sperm cell morphology and morphometry. Fertility was assessed by an artificial insemination trial. All in vitro parameters were analyzed by ANOVA. Heterogeneity test was scheduled for the fertility trial. After freezing-thawing process, motility and plasma membrane functionality were improved when SP was added. No differences were found for post-thaw viability between control and treatment samples. The percentage of normal cells was higher with SP at post-thawing, and a decrease of the presence of bent tailed spermatozoa with droplet in the SP group with respect to the control group was observed. Length of head spermatozoa was 3.4% higher in the samples with PBS compared to those which SP was added. Females pregnant at Day 25 post-insemination were 0/12 (with SP inside the straw) and 1/10 (without SP inside the straw). As conclusion, the presence of 10% SP at post-thawing, improves sperm cells motility, functionality and morphology, indicating that it would be beneficial to improve physiology of the frozen-thawed alpaca spermatozoa. More fertility trials must be developed to increase this knowledge.